1998
DOI: 10.1351/pac199870101985
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular chemistry at interfaces

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Measurement of the sulfur binding energy showed two peaks (Fig. 7), which represent discrete energies of a thiol [40] and a sulfonate [41] groups at 163 and 168 eV, respectively.…”
Section: Xps Measurementsmentioning
confidence: 99%
“…Measurement of the sulfur binding energy showed two peaks (Fig. 7), which represent discrete energies of a thiol [40] and a sulfonate [41] groups at 163 and 168 eV, respectively.…”
Section: Xps Measurementsmentioning
confidence: 99%
“…The use of noncovalent interactions at the solid−liquid interface provides an efficient and effective means of controlling the physical and chemical properties of surfaces . The ability to regulate noncovalent interactions between the surface and the modifier is an important tool for controlling the selectivity of the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…55 -56 A comparison of the response of the sulfide cavitand and octadecanethiol monolayers to organic vapours was measured by SPR spectroscopy. 24 ' 57 This indicated that each of the above vapours generally produced a response which was at least a factor of two greater for the cavitand monolayer. The only exception was C 2 C1 4 which produced a response twelve times greater for the cavitand monolayer.…”
Section: Binding Of Organic Amines From Aqueous Solution By Thin Filmmentioning
confidence: 97%
“…This result further supports guest/host molecular recognition of C2CI4 by the cavitand layer. 24 Crookes et al have demonstrated that/?-/er/-Bu-calix [4]arene 60 and p-tert-Bucalix [6]arene 61 attached to a reactive monolayer surface increased the adsorption Calixarenes in Action Downloaded from www.worldscientific.com by NANYANG TECHNOLOGICAL UNIVERSITY on 08/23/15. For personal use only.…”
Section: Binding Of Organic Amines From Aqueous Solution By Thin Filmmentioning
confidence: 99%